ANALISIS SISTEM ENTERPRISE RESOURCE PLANNING (ERP) TERHADAP KETERSEDIAAN BAHAN BAKU PT HJ BUSANA INDAH - Lestari, Viki; Indrawan, S.E., M.Ak, Andri; Noor., M.M, Drs. Iqbal (Jurnal Ilmu Akuntansi, 2023)
This ERP system aims to provide accurate information to help make decisions for a company. In this study, there was a case of loss of the main raw material at the company PT HJ Busana Indah. There are several presumptions regarding the loss of raw materials at PT HJ Busana Indah. The research method used in this writing is a qualitative approach with descriptive methods. Sources of data taken in this study were observations and interviews with employees of PT HJ Busana Indah. From the results of research and direct observation conducted at PT HJ Busana Indah related to Enterprise Resource Planning System Analysis on the Availability of Raw Materials, it can be concluded that the occurrence of cases of missing main raw materials is not due to an element of theft. However, due to negligence or human error, PT HJ Busana Indah employees made an efficient system run ineffectively. Keywords: Accounting Information System, Enterprise Resource Planning System, Warehouse management